2021
DOI: 10.1039/d1ob00661d
|View full text |Cite
|
Sign up to set email alerts
|

A concise/catalytic approach for the construction of the C14–C28 fragment of eribulin

Abstract: A diastereoselective gold cyclisation and a Sharpless asymmetric dihydroxylation–cycloetherification protocol were carried out for the construction of the key disaccharide unit (C14–C28) of eribulin mesylate with a linear sequence of 14 steps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Next, the 13 C NMR chemical shifts have been compiled to examine how the variation of the relative stereochemistry of the spirocenter/THF ring carbon will influence the chemical shifts of the other centers (Table 1). 3,9,10 It was noticed that the values of C2–C4 vary in all the diastereomers and that the stereochemistry at the spirocenter relative to the C3 had a significant effect. Coming to the change in the stereochemistry at C3, as one could notice (Table 1), it does not have any influence on the chemical shifts of the spiro-carbon.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, the 13 C NMR chemical shifts have been compiled to examine how the variation of the relative stereochemistry of the spirocenter/THF ring carbon will influence the chemical shifts of the other centers (Table 1). 3,9,10 It was noticed that the values of C2–C4 vary in all the diastereomers and that the stereochemistry at the spirocenter relative to the C3 had a significant effect. Coming to the change in the stereochemistry at C3, as one could notice (Table 1), it does not have any influence on the chemical shifts of the spiro-carbon.…”
Section: Resultsmentioning
confidence: 99%
“…1, this, taken together with our interest in the total synthesis of THF-containing natural products in general, and in the understanding of the 1 H/ 13 C chemical shift variation in corresponding diastereomers in particular, has led to the undertaking of the synthesis of the 5/5-spirocyclicketal core of these natural products. 3,4…”
Section: Introductionmentioning
confidence: 99%
“…Due to its wide application as an anti-cancerous agent, its total synthesis has been performed by different researchers using a number of strategies. Similarly, Senapati et al [ 132 ] in 2021 reported the total synthesis of C14–C28, central rings of eribulin, by using Sharpless asymmetric dihydroxylation, gold-catalyzed alkynol cyclization and cross metathesis. Within this framework, tetrahydropyran and tetrahydrofuran rings are linked via a glycosidic bond.…”
Section: Review Of the Literaturementioning
confidence: 99%